Analysis of Malaysian pepper market model - Fu Yee Kium, Nelson (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Malaysia is the fifth largest pepper exporter in the world. About 60% of the pepper produced in Malaysia is meant for export market. Malaysia exports both black pepper and white pepper in the international market. Sarawak Pepper is the trade name for pepper exported from Malaysia. The Malaysian pepper market model was developed to examine the interrelationship between the economic variables of supply, demand and price. The findings indicate that the important determinants of pepper prices are the stock levels and consumptions. The results also suggest that both Malaysian industrial production index and domestic price of pepper are key determinants of domestic demand for pepper in Malaysia. Finally, the domestic price of pepper is highly sensitive to its domestic consumption and its world price.